Effect of programmed Instruction Linear and Branched in learning the dribble and breast shooting skills in basketball - عناية الحسيناوي نهى (Journal of Physical Education, 2019)
Chapter one consisted of the introduction and the importance of study, the presentation of the problem, the aims and hypothesis. Chapter two consisted the theoretical studies related to study. It was pointed of the concept of programmed Instruction Linear and Branched, and dribble, breast shooting skills in basketball. Chapter three consisted the procedures and the study methods, where appointed at research methods, samples, pilot study, the main experiment, statisical methods used in the study. Chapter four focused on presentation of the result, analysis by using (T.Test), (F.Test) and (L.S.D) between the experiment and control group and discussion using the statistical method to explain the results. Chapter five conclusions and recommendation of the research, it is very important to use programmed Instruction Linear and Branched in learning of skills in basketball, and make more of the program of learning, more affective in this subject.